A method for preparing positive electrode material of lithium iron phosphate battery
Through a new preparation method, through hydrothermal reaction and the addition of nano-alumina, the shortcomings of the lithium iron phosphate battery cathode material in terms of low temperature and rate performance are solved, and the conductivity of the material and the service life of the battery are significantly improved, which is suitable for Industrial production.
Patent Information
- Application Number
- CN202311042796.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-18
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2043-08-18
AI Technical Summary
The existing lithium iron phosphate (LiFePO4) battery positive electrode materials have poor performance in low temperature and rate performance, and the battery life problem after multiple charges and discharges has not been effectively solved.
A new preparation method is adopted, by configuring lithium hydroxide solution and phosphoric acid for reaction, and then adding iron sulfate solution for hydrothermal reaction, controlling the pH value at 4.0 to 5.0, filtering and drying, adding nano-alumina dispersion and carbon-containing The organic matter is mixed, ball milled, and finally calcined in an inert atmosphere to obtain the lithium iron phosphate cathode material.
This method achieves uniform distribution of lithium iron phosphate nanoparticles, forms a good conductive network, improves the conductivity and cycle stability of the material, significantly extends the service life of the battery, and simplifies the process flow, making it suitable for industrial production.
Smart Images

Figure CN116812899B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new materials, and in particular to a method for preparing a positive electrode material for a lithium iron phosphate battery. Background Art
[0002] Lithium iron phosphate (LiFePO4) has been a hot topic in the research and development of lithium-ion battery positive electrode materials since its reversible lithium insertion and removal properties were first discovered in 1997 due to its good safety performance, long cycle life, wide source of raw materials, and no environmental pollution. It is recognized as one of the most promising lithium-ion power battery positive electrode materials.
[0003] LiFePO4 has an olivine structure, Pnma space group, and its lattice constants are a = 0.4699nm, b = 0.6011nm, c = 0.4699nm. In the crystal structure of LiFePO4, O atoms are tightly packed in a slightly distorted hexagonal shape, and P occupies the 4c position of the O tetrahedron to form a PO4 tetrahedron. Fe and Li occupy the 4c and 4a positions of the O octahedron, respectively, forming FePO6 and LiO6 octahedrons. Li forms a straight chain with a common edge at the 4a position and is parallel to the B axis, making Li + It can be freely deintercalated during the charge and discharge process, and the presence of the PO covalent bond prevents drastic volume expansion and contraction during the deintercalation of lithium.
[0004] At present, the main preparation methods of LiFePO4 include solid phase method, water / solvothermal method, sol-gel method, coprecipitation method, etc. Although LiFePO4 has been used in commercial batteries, there are still performance problems, such as low ion and electronic conductivity, which leads to poor low temperature performance and rate performance of LiFePO4 batteries, limiting the application of LiFePO4 in the next generation of lithium-ion batteries. In addition, the battery life after multiple charge and discharge has always been a problem to be solved. Summary of the invention
[0005] Purpose of the invention: People have tried to solve the above problems through different preparation methods. The present invention aims at the deficiencies in the prior art and provides a method for preparing a positive electrode material for a lithium iron phosphate battery.
[0006] Technical solution: prepare lithium hydroxide solution, then add phosphoric acid, and after sufficient reaction, obtain an intermediate product; prepare ferric sulfate solution, mix with the above intermediate product, and carry out hydrothermal reaction, and the pH value is controlled at 4.0-5.0. After the reaction is complete, filter, take the filter cake, wash and dry it, crush it, and ball mill it to obtain a powdered precursor;
[0007] Take 100 parts of the powdered precursor obtained above, add it to a reactor, then add 100-200 parts of nano-alumina dispersion, add 4-5 parts of carbon-containing organic matter, stir and mix, and control the temperature of the reactor between 90 and 100°C. Mix the mixture thoroughly to form a uniform mixture, emulsify it at high speed, spray dry it to obtain a powder, and finally calcine it under an inert atmosphere to obtain the lithium iron phosphate positive electrode material.
[0008] Specifically, the lithium hydroxide solution has a concentration of 2 mol / L, and the solvent is a mixture of ethylene glycol and water.
[0009] Specifically, the phosphoric acid addition rate is 0.01 mL / s.
[0010] Specifically, the concentration of the ferric sulfate solution is 0.3 mol / L.
[0011] Specifically, the hydrothermal reaction temperature is 140-200° C., and the time is 4-8 hours.
[0012] Specifically, the ball milling is dry ball milling, and the ball milling time is 5 to 10 hours.
[0013] Specifically, the nano-alumina dispersion is a dispersion of 5-10 nm alumina powder in a mixture of ethylene glycol and water, with the mass of alumina accounting for 10%. The present invention uses nano-alumina to increase the electrode area of the material, increase the electron transmission rate, and thus improve the conductivity of the material. At the same time, the use of nano-alumina can also prevent the tiny pores and defects inside the material from hindering electron transmission, thereby improving the cycle stability and charge and discharge efficiency of the material.
[0014] Specifically, the carbon-containing organic matter is oxalic acid. At a suitable temperature, the carbon decomposed by oxalic acid is dispersed at the atomic level in the reaction system, thereby achieving uniform coating of the synthetic product and forming an interconnected conductive carbon film between the particles; the in-situ coated carbon film in the solid phase synthesis reduces the growth rate of the lithium iron phosphate particles, thereby helping to effectively control the particle size of the positive electrode material.
[0015] Specifically, the high-speed shear emulsification has a rotation speed of 4000-6000 rpm, and the nano-scale and micro-scale particles in the slurry are evenly dispersed by the high-speed shear force, while preventing the agglomeration of large particles.
[0016] Specifically, the calcination temperature is 650-750° C. and the time is 5-10 hours.
[0017] As a further improvement, the ball milling is performed by wet ball milling, the ball milling time is 5 to 10 hours, the ball milling solvent is one of ethanol, a mixture of ethylene glycol and water, and a nano-alumina dispersion, and the ball milling is dried to obtain a powdered precursor. Preferably, a nano-alumina dispersion is selected, wherein the nano-alumina dispersion is a 5-10 nm alumina powder dispersed in a mixture of ethylene glycol and water, and the mass of the alumina accounts for 5%.
[0018] Beneficial effects: The method of the present invention achieves uniform mixing of materials and low-temperature reaction, effectively overcomes the defects of increased impurities and loss of active components caused by higher temperatures, and overcomes the shortcomings of uneven carbon source coating and poor material uniformity.
[0019] The lithium iron phosphate positive electrode material obtained by the preparation method of the present invention has lithium iron phosphate nanoparticles that are evenly distributed, have good contact conditions, and can form a good conductive network, which greatly enhances the conductivity of the lithium iron phosphate material and reduces the impedance of charge transfer. The performance of the lithium iron phosphate positive electrode material prepared by the preparation method is improved, and the service life of the battery is significantly improved.
[0020] The preparation method of the invention has a short flow, a simple process, is easy to operate, and is suitable for promotion to industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a scanning electron microscope image of the powdered precursor (1 μm).
[0022] Figure 2 This is a SEM image of the powdered precursor (5μm)
[0023] Figure 3 Scanning electron microscope image of lithium iron phosphate positive electrode material (1μm)
[0024] Figure 4 Scanning electron microscope image of lithium iron phosphate positive electrode material (3μm) DETAILED DESCRIPTION
[0025] The technical solution of the present application is described in detail below through embodiments, but the protection scope of the present application is not limited to the embodiments.
[0026] Example 1
[0027] Prepare a lithium hydroxide solution with a concentration of 2 mol / L (the solvent is a mixture of ethylene glycol and water), then add phosphoric acid at a rate of 0.01 mL / s. After sufficient reaction, an intermediate product is obtained; prepare a ferric sulfate solution with a concentration of 0.3 mol / L, mix it with the intermediate product, and perform a hydrothermal reaction at a temperature of 180°C for 6 hours, with the pH controlled at 4.0. After the reaction is complete, filter, take the filter cake, wash, dry, and crush it, and dry-mill for 8 hours to obtain a powdered precursor; its scanning electron microscope image is as follows Figure 1 and Figure 2 shown.
[0028] Disperse 5-10nm alumina powder in a mixture of ethylene glycol and water, with the mass of alumina accounting for 10%. Add 100 parts of the above powdered precursor into a reactor, add 200 parts of the above nano-alumina dispersion, and then add 5 parts of oxalic acid, stir and mix, and control the temperature of the reactor at 90°C. The reaction time is 6 hours. The mixture is fully mixed, and then subjected to high-speed shear emulsification at a speed of 5000rpm for 20 minutes. After spray drying, the powder is obtained, and finally calcined in an inert atmosphere at a calcination temperature of 700°C for 6 hours. The lithium iron phosphate positive electrode material is obtained. Its scanning electron microscope image is as follows Figure 3 and Figure 4 shown.
[0029] Example 2
[0030] Prepare a lithium hydroxide solution with a concentration of 2 mol / L (the solvent is a mixture of ethylene glycol and water), then add phosphoric acid at a rate of 0.01 mL / s. After sufficient reaction, an intermediate product is obtained; prepare a ferric sulfate solution with a concentration of 0.3 mol / L, mix it with the intermediate product, and perform a hydrothermal reaction at a temperature of 140°C for 4 hours, with the pH controlled at 4.0. After the reaction is complete, filter, take the filter cake, wash, dry, and crush it, and dry-mill for 5 hours to obtain a powdered precursor;
[0031] Disperse 5-10nm alumina powder in a mixture of ethylene glycol and water, with the mass of alumina accounting for 10%. Add 100 parts of the above powdered precursor into a reactor, add 100 parts of the above nano-alumina dispersion, and then add 4 parts of oxalic acid, stir and mix, while the reactor temperature is controlled at 90°C, the reaction time is 4 hours, the mixture is fully mixed, and then high-speed shear emulsification is performed at a speed of 4000rpm for 10 minutes, and the powder is obtained after spray drying, and finally calcined in an inert atmosphere at a calcination temperature of 650°C for 5 hours. The lithium iron phosphate positive electrode material is obtained.
[0032] Example 3
[0033] Prepare a lithium hydroxide solution with a concentration of 2 mol / L (the solvent is a mixture of ethylene glycol and water), then add phosphoric acid at a rate of 0.01 mL / s. After sufficient reaction, an intermediate product is obtained; prepare a ferric sulfate solution with a concentration of 0.3 mol / L, mix it with the intermediate product, and perform a hydrothermal reaction at a temperature of 200°C for 8 hours, with the pH controlled at 5.0. After the reaction is complete, filter, take the filter cake, wash, dry, and crush it, and dry-mill for 10 hours to obtain a powdered precursor;
[0034] Disperse 5-10nm alumina powder in a mixture of ethylene glycol and water, with the mass of alumina accounting for 10%. Add 100 parts of the above powdered precursor into a reactor, add 200 parts of the above nano-alumina dispersion, and then add 5 parts of oxalic acid, stir and mix, while the reactor temperature is controlled at 100°C, the reaction time is 6 hours, the mixture is fully mixed, and then high-speed shear emulsification is performed at a speed of 6000rpm for 30 minutes, and powder is obtained after spray drying, and finally calcined in an inert atmosphere at a calcination temperature of 750°C for 10 hours. The lithium iron phosphate positive electrode material is obtained.
[0035] Example 4 Performance Test
[0036] (1) The prepared lithium iron phosphate positive electrode material, binder (PVDF), and acetylene black were mixed in a mass ratio of 8:1:1, and then a certain amount of N-methylpyrrolidone (NMP) was added dropwise, and stirred evenly for 3 hours;
[0037] (2) Wipe the aluminum foil with anhydrous ethanol, then evenly coat the slurry on the surface of the aluminum foil, transfer the electrode to a vacuum drying oven, and vacuum dry at 120°C for 12 hours;
[0038] (3) The dried electrode pieces are lightly cold pressed and then punched to obtain electrode discs with a diameter of 16 mm;
[0039] (4) Assembly: Weigh each electrode and assemble the half-cell in a glove box with an argon atmosphere.
[0040] The electrochemical performance tests of lithium-ion batteries are as follows:
[0041] The battery was subjected to electrochemical impedance spectroscopy (EIS) testing on an electrochemical workstation with a test frequency range of 0.01 Hz to 100 KHz. The results are as follows:
[0042]
[0043]
[0044] Comparative Example 1 to Comparative Example 3
[0045] The steps of Comparative Examples 1 to 3 are substantially the same as those of Example 1, except that the carbon-containing organic matter is stearic acid. The reaction kettle temperatures of Comparative Examples 1, 2, and 3 are 80° C., 110° C., and 140° C., respectively. The positive electrode materials prepared in Comparative Examples 1 to 3 are tested using the method described in Example 4, and the results are as follows:
[0046]
[0047] Comparative Examples 4 to 6
[0048] The steps of Comparative Examples 4 to 6 are substantially the same as those of Example 1, except that the carbon-containing organic matter is glucose. The reaction kettle temperatures of Comparative Examples 4, 5, and 6 are 80° C., 110° C., and 140° C., respectively. The positive electrode materials prepared in Comparative Examples 4 to 6 are tested using the method described in Example 4, and the results are as follows:
[0049]
[0050] From the results, it can be seen that when stearic acid or glucose is selected as the carbon-containing organic matter, its conductivity is poor at a lower reaction temperature. When the reaction temperature is increased to above 120°C, although the conductivity is not much different, the capacity retention rate decreases significantly. The reason for this may be that when the reaction temperature increases, the incidence of side reactions increases, and the impurities produced will affect the life of the battery. At the same time, when the temperature rises, the active substances in the electrode material are easy to decompose or volatilize, which affects the conductivity and service life of the electrode material.
[0051] Comparative Example 7
[0052] The steps of Comparative Example 7 are substantially the same as those of Example 1, except that after forming a uniform mixture, the powder is directly spray-dried without undergoing high-speed shear emulsification.
[0053]
[0054] It can be seen that the conductivity of Comparative Example 7 is reduced, which may be due to the large particle agglomeration of lithium iron phosphate and the deformation of its crystal structure, which increases the defects inside the crystal, thus affecting the performance of the battery.
[0055] Example 5
[0056] The steps of Example 5 are substantially the same as those of Example 1, except that wet ball milling is used, the ball milling time is 8 hours, the ball milling solvent is ethanol, and the ball milling is followed by drying to obtain a powdered precursor.
[0057] Example 6
[0058] The steps of Example 6 are substantially the same as those of Example 1, except that wet ball milling is used, the ball milling time is 8 hours, the ball milling solvent is a mixture of ethylene glycol and water, and the product is dried after ball milling to obtain a powdered precursor.
[0059] Example 7
[0060] The steps of Example 7 are substantially the same as those of Example 1, except that wet ball milling is used, the ball milling time is 8 hours, the ball milling solvent is a nano-alumina dispersion, and the nano-alumina dispersion is prepared by dispersing 5-10 nm alumina powder in a mixture of ethylene glycol and water, with the mass of alumina accounting for 5%. After ball milling, the product is dried to obtain a powdery precursor.
[0061] Comparative tests were performed on Example 1, Example 5, Example 6, and Example 7, as follows:
[0062]
[0063] From the test results, it can be seen that when wet ball milling is used, the performance difference is not much, but the service life of the battery is significantly increased, which may be because the surface structure of the powdered precursor is changed, with a larger specific surface area, which has a favorable effect on the subsequent reaction. In addition, when the wet milling solvent is a nano-alumina dispersion, the battery performance is slightly improved compared with Example 1.
[0064] The above description is only a preferred embodiment of the present application and is not intended to limit the present application.
Claims
1. A method for preparing a positive electrode material for a lithium iron phosphate battery, characterized in that: The method comprises the following steps: preparing a lithium hydroxide solution, then adding phosphoric acid, and obtaining an intermediate product after sufficient reaction; preparing an iron sulfate solution, mixing the solution with the intermediate product, and conducting a hydrothermal reaction, wherein the pH value is controlled at 4.0 to 5.0, filtering after the reaction is complete, taking the filter cake, washing and drying the filter cake, crushing the filter cake, and ball milling the filter cake to obtain a powdered precursor; 100 parts of the powdered precursor obtained above are added to a reactor, and then 100-200 parts of a nano-alumina dispersion and 4-5 parts of a carbon-containing organic matter are added, and the mixture is stirred and mixed. At the same time, the temperature of the reactor is controlled between 90 and 100° C. The mixture is fully mixed to form a uniform mixture, and the mixture is emulsified at high speed and spray dried to obtain a powder, and finally calcined under an inert atmosphere to obtain the lithium iron phosphate positive electrode material; The carbon-containing organic matter is oxalic acid; The ball milling adopts wet ball milling, the ball milling time is 5 to 10 hours, and the ball milling is dried after the ball milling; the ball milling solvent is one of ethanol, a mixture of ethylene glycol and water, and a nano-alumina dispersion.
2. The method for preparing a positive electrode material for a lithium iron phosphate battery according to claim 1, characterized in that: The concentration of the lithium hydroxide solution is 2 mol / L, and the solvent is a mixture of ethylene glycol and water; the concentration of the ferric sulfate solution is 0.3 mol / L.
3. The method for preparing a positive electrode material for a lithium iron phosphate battery according to claim 1, characterized in that: The phosphoric acid addition rate was 0.01 mL / s.
4. The method for preparing a positive electrode material for a lithium iron phosphate battery according to claim 1, characterized in that: The hydrothermal reaction temperature is 140-200° C. and the reaction time is 4-8 hours.
5. The method for preparing a positive electrode material for a lithium iron phosphate battery according to claim 1, characterized in that: The nano-alumina dispersion is prepared by dispersing 5-10 nm alumina powder in a mixture of ethylene glycol and water, wherein the mass of the alumina accounts for 5-10%.
6. The method for preparing a positive electrode material for a lithium iron phosphate battery according to claim 1, characterized in that: The high-speed shear emulsification has a rotation speed of 4000-6000 rpm.
7. The method for preparing a positive electrode material for a lithium iron phosphate battery according to claim 1, characterized in that: The calcination temperature is 650-750°C and the time is 5-10 hours.
Citation Information
Patent Citations
Method for preparing lithium ion battery anode material spherical LiFePO4
CN101746742A
Lithium iron phosphate composite anode material in lithium-ion battery and preparation method thereof
CN102104149A